MENGAPA PERUSAHAAN WAJIB MELAKSANAKAN TANGGUNG JAWAB SOSIAL TERHADAP LINGKUNGAN Dilema perusahaan diantara negara, masyarakat dan pasar) - Budiono, Herlien (Jurnal Legislasi Indonesia, 2009)
A Limited Liability Company performing industrial activitiesin the area of energy sources, in particular that company whichprocesesses and in a productive way employs energy sources,has the responsibility which is known as the Responsibilityfor Social and Environment (Article 74 UUPT). The essence ofthe social responsibility is doing something good, either goodfor the company as also for the society.The role of the companywhich employs energy sources is that it should not only performindustrial activities, but also has its goal to go into the directionof fulfilling in the field of defeating global issues (polution,global warming, rescuing the world poverty, deforestation(caused by illegal logging) all for the good of mankind. Concreteand positive effort is needed to overcome these global issuessuch as giving incentives for companies in the field of wasterecyling, labour-intensive companies, information on one handbut also forbidding and supervising companies using materialswhich can cause polution on the other hand. It is of paramountimportance for Indonesia to strongly promote the internationallyaccepted technique of waste recycling on short term. A thoroughimplementation of this technique has shown to be a veryimportant means of rescue of the enviroment, and besidesthat it has also shown to be of an interesting economic value.Attitude and spirit of the family principle and solidaritybased on the principle of balance is embodied in theIndonesian people and UUPT.